The transfer of disability affairs from the state to the municipalities: With special emphasis on the largest municipality, Reykjavík - Freysteinsdóttir, Freydís Jóna; Jónsson, Gylfi (Veftímaritið Stjórnmál og stjórnsýsla, 2016)
The aim of this study was to examine how the transfer of the affairs of disabled people from the state to the municipalities had proceeded. The process of the transfer was examined and then the largest municipality, Reykjavík, was chosen for a closer examination on the policy and implementation concerning services for disabled people. A qualitative study was conducted in the autumn of 2012. Eight interviews were taken with key professionals who had been involved directly in the transfer or worked on the affairs of disabled people before or after the transfer. A specialist in the affairs of disabled people was interviewed at the Ministry of Welfare and at the Association of Local Authorities in Iceland. Furthermore, a key professional was interviewed in each of the six municipal services in Reykjavík. The interviewees believed that having decided on and gone through with the transfer was the right thing to do. They believed that services closer to the people who need it would be a better choice. The person that uses the services only needs to go to one place in order to receive it, instead of two as before. However, the interviewees had not seen a considerable improvement in the services as expected. A considerable additional funds are needed for the affair. The transition from the state to the municipalities was not sufficiently prepared. The affairs of disabled people requires a lot of interdisciplinary work as well, which the interviewees thought was proceeding well. Markmið rannsóknarinnar var að skoða hvernig yfirfærsla á málaflokki fatlaðs fólks frá ríki til sveitarfélaga hefði gengið fyrir sig. Heildarferli yfirfærslunnar var skoðað og síðan var eitt sveitarfélag, Reykjavíkurborg, valið og skoðað nánar með tilliti til stefnu og framkvæmdar á þjónustunni við fatlað fólk. Um var að ræða eigindlega rannsókn sem fór fram haustið 2012. Tekin voru átta viðtöl við fagaðila sem höfðu komið beint að vinnu við yfirfærsluna eða unnið við málaflokkinn fyrir og eftir yfirfærslu. Tekið var viðtal við starfsmenn hjá ...